ANALISIS PERBANDINGAN Z-SOURCE DC-DC BOOST CONVERTER DENGAN BOOST CONVERTER - Iqbal Achmad Gautawa; Rini Nur Hasanah; Lunde Ardhenta (Jurnal Mahasiswa TEUB, 2022)
This paper describes the simulation design of a boost converter that has a high voltage gain. High voltage gains are obtained using the new z-source dc-dc boost converter topology circuit. This converter uses an impedance network which is used as a bridge between the source and the converter. The Z-source converter overcomes the conceptual, theoretical and limitations of conventional voltage source converters and current source converters. The stress on the diodes and switches is lower than the boost converter, so efficiency is improved. At a low duty cycle, this converter is able to produce a higher voltage gain than the boost converter. Both converters are then tested with the same specifications with the aim of knowing the output comparison between the two converters. The test of the two converters is simulated with the PSIM application and analyzed at several stages of testing. The test includes the specifications of the components used, analysis of each component in transient and steady state conditions, comparison of the voltage gain tested at varying duty cycle values, as well as calculation of voltage stress and current stress on the z-source converter and boost converter circuits.Keywords: boost converter, z-source converter, high voltage gain, voltage stress, current stress, PSIM